2022
DOI: 10.1371/journal.pcbi.1009824
|View full text |Cite
|
Sign up to set email alerts
|

Analytical kinetic model of native tandem promoters in E. coli

Abstract: Closely spaced promoters in tandem formation are abundant in bacteria. We investigated the evolutionary conservation, biological functions, and the RNA and single-cell protein expression of genes regulated by tandem promoters in E. coli. We also studied the sequence (distance between transcription start sites ‘dTSS’, pause sequences, and distances from oriC) and potential influence of the input transcription factors of these promoters. From this, we propose an analytical model of gene expression based on measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 61 publications
(101 reference statements)
0
18
0
Order By: Relevance
“…Tandem promoters significantly improve gene expression levels. , Herein, the copy number of P aprE was optimized to promote the transcriptional strength of keratinase at the enzyme-producing stage. Recombinant strains harboring single to quadruplex copies of the P aprE promoter were constructed and were selected based on keratinase activity.…”
Section: Resultsmentioning
confidence: 99%
“…Tandem promoters significantly improve gene expression levels. , Herein, the copy number of P aprE was optimized to promote the transcriptional strength of keratinase at the enzyme-producing stage. Recombinant strains harboring single to quadruplex copies of the P aprE promoter were constructed and were selected based on keratinase activity.…”
Section: Resultsmentioning
confidence: 99%
“…We assumed the classification of GR in (67,68) as an input TF that regulates a large number of genes that rarely regulate themselves and participate in metabolic pathways. Meanwhile, we did not account for promoters’ close proximity (e.g., tandem formation), since a recent study (69) showed that, under similar stress, while close proximity causes transcription interference (reducing overall transcription levels), it does not influence if a gene is up- or down-regulated by input TFs.…”
Section: Resultsmentioning
confidence: 99%
“…However, a detailed molecular biological explanation for this phenomenon is still lacking. It is worth mentioning that in E. coli , 831 genes have been found to be under the control of tandem promoters ( 65 ), suggesting the broadness of the regulatory scheme. Hence, in-depth research on modeling molecular events in the transcription process is needed to elucidate the effect of promoter architecture on expression noise.…”
Section: Discussionmentioning
confidence: 99%